A transient hydro-thermo-bubble model for gas kick simulation in deep water drilling based on oil-based mud. (25th July 2019) - Yang, Hongwei; Li, Jun; Liu, Gonghui; Jiang, Hailong; Wang, Chao; Jiang, Jiwei
Highlights: A two-phase flow model is developed for gas kick simulation in oil-based mud. The interphase mass transfer rate is quantified using bubble hydraulics. Mass and heat transfer and bubble-bubble interaction are mutually coupled. Mass and heat transfer and bubble-bubble interaction impact the gas evolution. Abstract: Accurate prediction of wellbore gas-liquid two-phase flow behaviors is significant for gas kick detection and well control treatment, particularly in oil-based mud. Considering the synergy of mass transfer, heat transfer and bubble-bubble interaction, a fully coupled hydro-thermo-bubble model was developed to simulate the wellbore gas-liquid two-phase flow during gas kick in oil-based mud. In this model, the impact of gas flow on heat transfer was considered. Also, the variation in the gas concentration in the mass transfer boundary layer based on the bubble hydrodynamics was used to quantify the mass transfer rate. The integrated model was solved using the fully-implicit finite difference method. The accuracy and capability of the model were verified using the field and experimental measurement data. Using this model, the wellbore two-phase flow behaviors and temperature distribution characteristics during gas kick in oil-based mud were analyzed. Additionally, the mutually coupled effects between mass transfer, heat transfer and bubble-bubble interaction were investigated. Moreover, the impacts of mass transfer, heat transfer and bubble-bubble interaction on two-phase flow characteristics were compared.